Blindness and reorientation problems in Plato's Republic - Reeve, C. D. C., 1948- (New York : Oxford University Press, 2013)
C.D.C. Reeve develops a powerful new account of the age-old argument over whether the just are happier than the unjust drawing from a new understanding of Plato's conception of philosophy.
Description based on online resource; title from home page (viewed on Dec. 20, 2012).
Includes bibliographical references and index.
Keywords: Plato